Wide excision as an optional treatment for large ossifying fibroma: a case report - Hadira Hadira; Adiantoro Seto; Endang Syamsudin (Journal of Dentomaxillofacial Science, 2019)
Objective: Ossifying fibromas is a benign type of fibro-osseous tumor. These lesions may arise in the maxillary or mandible, but generally have more predilection of the mandible. Women are more often affected.Methods: A female patient, aged 40 years old, came to the Oral and Maxillofacial Polyclinics at Hasan Sadikin Hospital, complaining of a lump in the upper jaw. The lump effect makes the face asymmetrical, painless and has a hard consistency. We diagnosed this patient with ossifying fibroma. Ossifying fibroma is a kind of lesion that can spread to all directions, so it can resemble a sphere shape. Enucleation and curettage are the common treatment. Larger lesions, which have significant expansion or aggressive growth features, may require resection or wide excision Results: In this case our treatment ossifying fibroma is wide excision with ferguson webber incision technique and good results.Conclusion: Ossifying fibromas is a benign type of fibro-osseous tumor. Wide excision is an option for a large size of ossifying fibroma.